Thermal Decomposition Study of Ferrocene [(C5H5)2Fe]. (27th April 2014) - Bhattacharjee, Ashis; Rooj, Amlan; Roy, Debasis; Roy, Madhusudan
Abstract : A single-step thermal decomposition of ferrocene [(C5 H5 )2 Fe] using nonisothermal thermogravimetry (TG) has been studied using single- as well as multiple-heating rate programs. Both mechanistic and nonmechanistic methods have been used to analyze the TG data to estimate the kinetic parameters for the solid state reaction. Two different isoconversional methods (improved iterative method and model-free method) have been employed to analyze the TG results to find out whether the activation energy of the reaction depends on the extent of decomposition and to predict the most probable reaction mechanism of thermal decomposition as well. A comparison of the activation energy values for the single-step thermal reaction of ferrocene estimated by different methods has been made in this work. An appraisal on the applicability of single-heating rate data for the analysis of single-step thermal decompositions over the recommendations by the International Confederation for Thermal Analysis and Calorimetry (ICTAC) is made to look beyond the choice.